How do children with phonological impairment respond to requests for clarification containing polysyllables?. (October 2014) - Masso, Sarah; McCabe, Patricia; Baker, Elise
Accurate production of polysyllables (words of three or more syllables) can be challenging for children with phonological impairment. Research with typically developing children has suggested that children can improve their polysyllable productions in response to requests for clarification containing an incorrect model of a target word (Gozzard et al., 2008). This study extends the work of Gozzard et al. (2008) by determining whether accuracy can improve in response to requests for clarification containing a correct (e.g. 'did you say elephant?') versus an incorrect (e.g. 'did you say eresemp?') model. Four children with phonological impairment (aged 3;10, 3;11, 4;3 and 5;4) had segmental and structural difficulties with polysyllables, in both single word and connected speech contexts. All participants revised their productions following requests for clarification containing the incorrect production, with 75.8% of suprasegmental and phonological revisions demonstrating increased accuracy. No phonological or suprasegmental revisions occurred following requests for clarification containing the correct model. The findings suggest that role of communication breakdown and repair in intervention targeting children's polysyllable difficulties needs to be better understood.